Partido e educação: as contribuições do Partido Comunista Brasileiro para a educação (1958-1964). - Tulio Cesar Dias Lopes (2016)
The educational debate found in the field of Marxist culture the possibility of linking itself to the perspective of social revolution. Many revolutionaries, intellectuals and researchers propose to investigate and suggest alternatives in relation to the issue of education. For nearly two centuries, the questions raised by Marxism are in constant development, being debated by many scholars and activists. The Brazilian Communist Party (PCB), the leading exponent of Communist Political Culture in Brazil, contributed decisively in the struggle for public education. The main objective of this research was to analyze the contributions of PCB for education between 1958 and 1964. Through a theoretical bibliographic and documentary research, we sought to establish some connections between the socialist/communist ideology and education, understood by the party as a task of political formation of its leaders and members, the educational work and "political education" of the class which they identified themselves with and, tactically, the struggle for the democratization of access to public education. We conclude that, on one hand, the party consideredthe formation of its members and leaderships in the Marxist-Leninist"doctrine" asa political and organizational priority On the other hand, through their instruments of agitation and propaganda (newspapers and magazines), PCB sought to contribute to the raising of consciousness of the working class and the Brazilian people. The party linked its conception of education with the democratic national strategy of the Brazilian Revolution. We present these contributions in the theoretical debate as well as the proposals and actions developed by the Brazilian communists in the period.